1001 A new model of spontaneous anti-phospholipid antibody induced pregnancy loss in mice over-expressing human TLR8. (14th December 2022) - Maria, Naomi I; Martinez, Shani; Raparia, Chirag; Yi, Zhengzi; Tao, Haiou; Lin, Ke; Zhang, Weijia; Davidson, Anne
Abstract : Background: Systemic Lupus Erythematosus (SLE) predominantly affects women of childbearing age and is associated with adverse pregnancy outcomes including pre-eclampsia, placental abnormalities and fetal mortality, particularly in the presence of antiphospholipid antibodies (aPL). Pathogenic mechanisms damaging the fetal-maternal unit, however, remain poorly understood. Recent studies have implicated endosomal Toll-like receptor 8 (TLR8) in mediating pregnancy loss by amplifying the release of pro-inflammatory cytokines from human placental trophoblasts exposed to APL antibodies in vitro. However, to date there has been no reliable spontaneous model of APL antibody induced placental injury and the role of TLR8 in either systemic autoimmunity or placental injury has remained elusive as TLR8 function differs from mouse to man. We report here the development of a novel model of spontaneous fetal loss due to expression of human TLR8 (huTLR8) in Sle1 mice with APL autoantibodies. Our work indicates that this is due to a placental developmental defect that is associated with loss of the placental junctional zone and attenuated development of placental vasculature leading to placental ischemia, placental inflammation and fetal loss. Methods: huTLR8 transgenic (tg) Sle1 mice were generated and followed clinically. Non- transgenic littermates were used as controls. huTLR8 DNA copy number and mRNA expression was confirmed by qDigital- and qRT-PCR and huTLR8 function was confirmed by measuring BM derived macrophage responses to TLR8 agonists. Timed pregnancies were closely followed and placentas were harvested at Days 8.5, 13.5 and from mice exhibiting signs of dystocia/prolonged labor at Day 20-21. Pup and placental weight was assessed. Placental tissues were characterized by H&E and myeloperoxidase (MPO) staining to identify neutrophils. Inflammatory cytokine expression was assessed in placental tissue by qPCR. Splenic and placental immune populations were analyzed using flow cytometry. Neutrophil netting was evaluated after exposure to PMA or TLR8 agonists. Bulk RNASeq was performed on Day 8.5 fetal-placental units and Day 13.5 placentas. Results: We observed a high frequency of maternal and fetal death in both huTLR8tg heterozygous and homozygous dams. Maternal death was due to dystocia as a result of intrauterine growth retardation and failed delivery of non-viable pups. Genotyping of resorbed pups revealed no difference in the percentage of resorbed males and females. Fetal resorptions did not occur in wild type Sle1 or huTLR8tg.C57BL/6 females. Litter size was also smaller in successful huTLR8tg pregnancies than in control pregnancies with no difference in the ratio of male:female pups. IL-6, TNF? and MPO mRNA expression was significantly increased in placentas of affected litters and negatively correlated with placental weight. TNF deficiency did not prevent dystocia in transgenic dams. Abnormal placental morphology included loss of the placental junctional zone, placental infarcts, loss of placental lakes, arterial wall thickening and increased MPO+ netting neutrophils. In vitro neutrophil netting in response to TLR8 agonists was not increased. Observation of timed pregnancies showed that implantation was successful at Day 8.5 but that fetal resorptions began to occur between Day 8.5 and Day 13.5. RNA sequencing of the fetal-placental unit at Day 8.5 revealed a significant decrease in expression of pregnancy associated glycoproteins from the CEACAM family; these are synthesized by junctional zone trophoblasts and mediate placental angiogenesis. In addition, there was a decrease in NK cell markers, suggesting a failure of recruitment of these cells to the maternal decidua. By contrast, expression of inflammatory markers was upregulated. These differences persisted in Day 13.5 placentas with a decrease in cytolytic programs. Upregulated genes of interest at Day 13.5 included Prl4a1 that negatively regulates NK cell cytolytic function and Phlda2 that negatively regulates the size of the junctional zone. Conclusions: Here we identify a new model to study adverse pregnancy complications in SLE and APS. In the presence of both Sle1 and huTLR8, we observed early onset of aPL autoantibodies and spontaneous pregnancy loss due to fetal resorption/dystocia, resulting in both fetal and maternal death attributed to placental developmental abnormalities already present by Day 8.5 that caused decreased placental vascularization, placental infarcts and inflammation. This new model may be useful to study mechanisms of pregnancy loss in anti- phospholipid syndrome.